2011
DOI: 10.1111/j.1474-9726.2011.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Myosin light chain 3f attenuates age‐induced decline in contractile velocity in MHC type II single muscle fibers

Abstract: Summary Aging is characterized by a progressive loss of muscle mass and impaired contractility (e.g., decline in force, velocity, and power). Although the slowing of contraction speed in aging muscle is well described, the underlying molecular mechanisms responsible for the decrement in speed are unknown. Myosin heavy chain (MHC) isoforms are the primary molecules determining contractile velocity; however, the contraction speed of single fibers within a given MHC isoform type is variable. Recent evidence propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 29 publications
(39 reference statements)
5
35
0
1
Order By: Relevance
“…Absence of the N-terminal extension generates lower force (41), probably causing a less prominent power stroke in S1A2, and is not related to abnormal cardiac function. On the other hand, in the skeletal muscle of aged rats, replacement of A1 in a fraction of heads by A2 improved contractility by increasing the rate of shortening (43). This is consistent with the hypothesis that the N-terminal extension enhances isometric force while slowing the speed of unloaded shortening.…”
Section: Discussionsupporting
confidence: 79%
“…Absence of the N-terminal extension generates lower force (41), probably causing a less prominent power stroke in S1A2, and is not related to abnormal cardiac function. On the other hand, in the skeletal muscle of aged rats, replacement of A1 in a fraction of heads by A2 improved contractility by increasing the rate of shortening (43). This is consistent with the hypothesis that the N-terminal extension enhances isometric force while slowing the speed of unloaded shortening.…”
Section: Discussionsupporting
confidence: 79%
“…Tikunov et al have also found a shift from fast to slow myosin light chain, tropomyosin, and troponin (C, I, and T) isoforms in CHF. Aging causes a decrease in the fast myosin light chain 3 isoform in limb muscle that contributes to slow shortening velocity [115], and this may also occur in the diaphragm. Overall, MHC and thin-filament protein adaptations will compromise diaphragm function during expulsive behaviors as fibers with slow myofibrillar protein isoforms have slower shortening velocity and lower peak power than fibers rich in fast isoforms.…”
Section: Intrinsic Diaphragm Muscle Abnormalitiesmentioning
confidence: 99%
“…There are two regulatory (MLC2s, MLC2f) and three essential (MLC1s, MLC1f, MLC3f) isoforms that typically are found in slow-twitch (s or MHC I) and fast-twitch (f or MHC II) fibers, although various combinations of these isoforms are found. The relative proportion of MLCs expressed in individual human fibers does not seem to affect cross-bridge kinetics (17), although it may regulate function in the fastest fibers in lower order mammals (12). On this background, we will now discuss how aging and disease might alter skeletal muscle performance by modulating these molecular functional properties.…”
Section: Myofilament Protein Content and Functionmentioning
confidence: 99%